2007
DOI: 10.1073/pnas.0709701104
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the diffraction barrier outside of the optical near-field with bright, collimated light from nanometric apertures

Abstract: The optical diffraction limit has been the dominant barrier to achieving higher optical resolution in the fields of microscopy, photolithography, and optical data storage. We present here an approach toward imaging below the diffraction barrier. Through the exposure of photosensitive films placed a finite and known distance away from nanoscale, zero-mode apertures in thin metallic films, we show convincing, physical evidence that the propagating component of light emerging from these apertures shows a very str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Another possibility is integrated sub-wavelength light sources that provide near-field optical imaging. 15,65…”
Section: Future Directionsmentioning
confidence: 99%
“…Another possibility is integrated sub-wavelength light sources that provide near-field optical imaging. 15,65…”
Section: Future Directionsmentioning
confidence: 99%
“…At values of z > 6 μm, the intensity of the transmitted radiation decreased and there is no appearance of a clear second image revival plane as predicted by traditional Talbot theory. Hence, it appears that the transmitted field is modulated in a striking manner along the z -axis . The intensity profiles demonstrate that these nanohole arrays can cause the propagating light to constructively and destructively interfere, creating “dark” and “light” zones that can extend to large distances along the propagation axis.…”
Section: Resultsmentioning
confidence: 99%
“…Hence it appears that the transmitted field is modulated in a striking manner along the z-axis. 40 The intensity profiles demonstrate that these nanohole arrays can cause the propagating light to constructively and destructively interfere creating “dark” and “light” zones that can extend to large distances along the propagation axis.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, MLA is operating in an optical region between the near field and far field, resulting in an optical mesofield with the coexistence of evanescent wave and propagating wave. Recent research on bioimaging also demonstrated that the super-resolution can be achieved to overcome the optical diffraction limit in an optical mesofield [108]. However, the detailed physics is still not very clear.…”
Section: Microlens Array (Mla) Nanolithographymentioning
confidence: 99%